The Implementation of the Visual, Auditory, Kinesthetic (VAK) Learning Model to Improve Students' Learning Motivation in Science and Social Studies (IPAS) for Grade V at UPTD SD Negeri 45 Parepare - Musfirah, Musfirah; Zaid Zainal; Aisyah Ramadana (International Journal of Technology and Education Research, 2025)
The main problem in this study is the low quality of the learning process and students' learning motivation in Grade V. This study aims to improve the learning process and students’ learning motivation. The approach used is a qualitative approach with a classroom action research (CAR) design. The research subjects consisted of one teacher and 19 students of Grade V at UPTD SDN 45 Parepare in the 2024/2025 academic year, including 13 male students and 6 female students. The research was carried out in two cycles, with four stages: planning, implementation, observation, and reflection. Data were collected through observation, documentation, and questionnaires. The results of the study concluded that the implementation of the Visual, Auditory, Kinesthetic (VAK) learning model can improve the quality of the learning process. This is evident from the increased student engagement in the learning process, better focus and cooperation among students in completing group tasks, as well as a more enjoyable classroom atmosphere. The quality of the learning process and students’ learning motivation were found to improve, as shown by the questionnaire data filled in by the students. In Cycle I, the observations of the learning process and students’ motivation were categorized as Fair (C), while in Cycle II, both the teacher’s learning process aspect and students’ learning motivation improved to the Good (B) category. In conclusion, the implementation of the VAK learning model can enhance the learning process and students’ learning motivation in IPAS learning.